Kajian Bentuk Rumoh Aceh Di Desa Rumpet - Yulia. R; Zia Faizurrahmany El Faridy (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Rumoh Aceh is a traditional building that is one of the cultures and identities of Aceh. Partly in Rumpet Village, Aceh Besar Regency, there are several Acehnese houses that are still being lived in. Rumoh Aceh in Rumpet Village totals 9 units, and all of them are occupied as residential houses. The problem in this research is how the shape change and typology of the form of Aceh rumoh in Rumpet Village.